Repetitive or Innovative? Children's Literature in Translation as the Main Focus of B.A. And M.A. Theses - Anna Fornalczyk-Lipska (University Babes-Bolyai, 2022)
The first two decades of the twenty-first century may be rightly described as a blooming period of Children's Literature Translation Studies (CLTS). This is true for the situation in many countries, including Poland. The steadily growing interest in this subdiscipline is also visible in the teaching offer of many universities, and in the choice of thesis topics chosen by B.A. and M.A. students of modern philology or linguistics. The goal of this paper is to analyse those B.A. and M.A. theses which focused on translated children's literature within the last ten years at the University of Warsaw. The basis for the study is an analysis of the Graduate Theses Archives (APD), including thesis titles, keywords, and abstracts. In the analysis, the following aspects are examined: the research profile chosen by the students, the interdisciplinary character of the theses, their range of topics, as well as source and target languages considered. The paper will try to answer the questions as to how B.A. and M.A. students perceive the potential of analysing translated children's literature within the broader field of translation studies, to what extent the issues they spotlighted reflect more advanced forms of academic work in CLTS, and how the topics relate to James Holmes' "map" of Translation Studies and Göte Klingberg's classification of research areas in the more specific field of translated children's literature.